2000
DOI: 10.1007/s004290050332
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube closure in humans initiates at multiple sites: evidence from human embryos and implications for the pathogenesis of neural tube defects

Abstract: The closure of the neural tube (NT) in the human embryo has generally been described as a continuous process that begins at the level of the future cervical region and proceeds both rostrally and caudally. On the other hand, multiple initiation sites of NT closure have been demonstrated in mice and other animals. In humans, based on the study of neural tube defects (NTD) in clinical cases, van Allen et al. (1993) proposed a multisite NT closure model in which five closure sites exist in the NT of human embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
107
0
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(115 citation statements)
references
References 22 publications
4
107
0
4
Order By: Relevance
“…The existence of closure 2 in humans is controversial. Some human studies have observed a closure point around the forebrain/ midbrain boundary, and other groups have postulated its existence based on the types of NTDs that exist in the human population (30,40). Others, however, have reported an absence of closure point 2 (32, 37).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of closure 2 in humans is controversial. Some human studies have observed a closure point around the forebrain/ midbrain boundary, and other groups have postulated its existence based on the types of NTDs that exist in the human population (30,40). Others, however, have reported an absence of closure point 2 (32, 37).…”
Section: Discussionmentioning
confidence: 99%
“…The lateral edges of the neural plate elevate to form the neural folds and they fuse to form the neural tube. The fusion of the neural folds initiates at several sites in mammalian embryos, although the mode of neural tube closure may be different among species (Van Allen et al, 1993;Juriloff and Harris, 2000;Nakatsu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The two most common NTDs are spina bifida (17.9 per 100,000 live births in the United States) and anencephaly (11.11 per 100,000 live births in the United States; CDC, 2007). Spina bifida, which affects 1,500-2,000 newborns every year in the United States, results from a failure of the neural tube to close properly, a process that is normally completed at 28 days of gestation in humans (AACC, 2007;Keller-Peck and Mullen, 1997;Nakatsu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%